Group Rewards and Individual Sanctions in Environmental Policy - Bouwe R. Dijkstra; Dirk T.G. Rübbelke (Fondazione Eni Enrico Mattei (FEEM), 2007)
We examine an incentive scheme for a group of agents, where all agents are rewarded if the group meets its target. If the group does not meet its target, only the agents that meet their individual target are rewarded. In environmental policy, the EU burden sharing agreement and the UK Climate Change Agreements feature this incentive scheme. There is only a difference in outcome between group and individual rewards if emissions are stochastic. Group rewards generally lead to higher expected emissions than individual rewards. The attraction of the group reward scheme may lie in its fairness and its tough-looking targets.
Keywords: Q54; Q58; 330; Team Incentive Scheme; Stochastic Pollution; UK Climate Change Agreements; Klimaschutz; Entscheidung; Stochastischer Prozess; Nichtkooperatives Spiel; Umweltpolitik; Großbritannien; EU-Umweltpolitik; EU-Staaten